2009
DOI: 10.1143/apex.2.121102
|View full text |Cite
|
Sign up to set email alerts
|

Halide Vapor Phase Epitaxy of MgxZn1-xO Layers on Zn-Polar ZnO Substrates

Abstract: High quality Mg x Zn 1Àx O layers (0 x 0:16) on Zn-polar ZnO substrates were successfully grown by halide vapor phase epitaxy (HVPE) at a high temperature of 1000 C. The Mg x Zn 1Àx O layers exhibited atomically flat surfaces, and were free from impurities. The near-bandedge emission of photoluminescence (PL) at room temperature could be varied from 3.26 to 3.56 eV with increase of the Mg concentration. PL measurements at 12 K revealed that a Mg 0:16 Zn 0:84 O layer grown by HVPE exhibited excellent optical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Precise control of the solid composition of Mg x enhances the opportunity to apply Mg x Zn 1Àx O in various applications, including light-emitting or receiving devices for the UV spectral region, 3,4) and for two-dimensional structures. 5) Recent reports suggest that changes in the lattice constant of Mg x Zn 1Àx O from that of ZnO could be small, [6][7][8] a property that will render Mg x Zn 1Àx O/ZnO structures suitable for virtually strain-free bandgap engineering. 9) When growing compound semiconductor alloys by VPE, the unambiguous relationship between the supplied gaseous composition and the solid composition is of importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precise control of the solid composition of Mg x enhances the opportunity to apply Mg x Zn 1Àx O in various applications, including light-emitting or receiving devices for the UV spectral region, 3,4) and for two-dimensional structures. 5) Recent reports suggest that changes in the lattice constant of Mg x Zn 1Àx O from that of ZnO could be small, [6][7][8] a property that will render Mg x Zn 1Àx O/ZnO structures suitable for virtually strain-free bandgap engineering. 9) When growing compound semiconductor alloys by VPE, the unambiguous relationship between the supplied gaseous composition and the solid composition is of importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported epitaxial ZnO and Mg x -Zn 1Àx O growth in a HVPE system using ZnCl 2 and H 2 O as source gases, 8,10) and have demonstrated that ZnO and Mg x Zn 1Àx O can be grown at the high temperature of 1000 C without any significant degradation of the growth rate. A thermodynamic approach to the ZnCl 2 -H 2 O system can well explain the dependence of growth rate on the growth conditions.…”
Section: Introductionmentioning
confidence: 99%